When They Go Low, We Go High? : Measuring Bank Market Power in a Low-for-Long Environment. (Washington, D.C. : International Monetary Fund, 2021)
We examine trends in bank competition since the early 2000s. The Lerner index-arguably the most commonly used measure-shows evidence of a marked increase in market power in advanced economies, especially after the global financial crisis. But other frequently used indicators of banking sector competition seem much more muted. We show that the significant drop in policy rates that occurred in the aftermath of the crisis could explain the seeming disconnect. Adjusting the Lerner index for the impact of policy rates reveals that market power has been fairly constant in advanced economies-consistent with the other signals and similar to the pattern observed in emerging markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; Underground Econom